Changes in the Velocity of Blood in the Portal Vein in Mild Acute Pancreatitis—A Preliminary Clinical Study - Artautas Mickevičius; Jonas Valantinas; Juozas Stanaitis; Tomas Jucaitis; Laura Mašalaitė (Medicina, 2019)
Background and objective: Portal vein thrombosis is associated with a decrease in the main blood velocity in this vessel. While most studies examine etiological factors of portal vein thrombosis after its occurrence, we aimed to evaluate portal vessels and assess whether mild acute pancreatitis affects blood flow in the portal vein and increases the risk of thrombosis. Materials and methods: This prospective single centered follow-up study enrolled 66 adult participants. Fifty of them were diagnosed with mild acute pancreatitis based on the Revised Atlanta classification, and 16 healthy participants formed the control group. All participants were examined three times. The first examination was carried out at the beginning of the disease and the next two at three-month intervals. Blood samples were taken and color Doppler ultrasound performed the first time, whereas ultrasound alone was performed during the second and third visits. Mean and maximal blood velocities and resistivity index in the main portal vein and its left and right branches were evaluated. Results: Mean velocity of the blood flow in the main portal vein and its right and left branches was not significantly different from healthy individuals during the acute pancreatitis phase: 23.1 ± 8.5 cm/s vs. 24.5 ± 8.2 cm/s (p = 0.827); 16.4 ± 7.9 cm/s vs. 16.4 ± 8.1 cm/s (p = 1.000); and 8 ± 3.4 cm/s vs. 7.4 ± 2.5 cm/s (p = 0.826), respectively. The same was observed when comparing the maximal blood flow velocity: 67.9 ± 29 cm/s vs. 67.5 ± 21 cm/s (p > 0.05); 45.4 ± 27 cm/s vs. 44 ± 23.8 cm/s (p = 0.853); and 22.2 ± 9.8 cm/s vs. 20 ± 7.3 cm/s (p = 0.926), respectively. Changes in venous blood velocities were not significant during the follow-up period in separate study groups. Conclusions: Portal blood flow velocities do not change during mild acute pancreatitis in the inflammatory and postinflammatory periods. This observation suggests that mild acute pancreatitis does not increase the risk of portal vein thrombosis.